Pengaruh Penyerapan Eceng Gondok (Eichornia crassipes) Dan Apu Apu (Pistia stratiotes) Terhadap Konsentrasi Cu Dan Zn Pada Air Limbah Pertambangan PT J Resources Bolaang Mongondow - Rendy Stewart Wajong; Bobby Polii; Wieske Chriesti Rotinsulu (Sam Ratulangi University, 2022)
This research aims to analyze the concentration of Cu, Zn, and pH in mining wastewater at the Pit Osela of PT J Resources Bolaang Mongondow (JRBM) and the effect of absorption of water hyacinth (eichhornia c) and water lettuce (pistia stratiotes) on heavy metals Cu, Zn and pH in plant tissues. Research Methods: The study was located in PT JRBM's greenhouse in Bolaang Mongondow Regency with Mining Wastewater (ALP) in Pit Osela (mining). The results: Cu concentration in ALP Pit Osela in the initial condition was 15.59 mg/l. The decrease in Cu concentration by water hyacinth started from 7.02 mg/l to 15.48 mg/l with an effectiveness of 45% to 99.3%. The concentration of Cu after being given water lettuce on the third day (38 days) was 0.12 mg/l. The concentration of Cu on the third day group was 8.51 mg/l. The concentration of Zn in ALP in Pit Osela (mining area) in the initial condition was 7.03 mg/l, after being given water hyacinth and water lettuce on the third day (38 days) it became 0.00 mg/l. The concentration of Zn in the control group on the first day was 7.01 mg/l, on the third day it was 7.01 mg/l. The pH concentration of ALP in the Osela Pit in the initial condition was 3.03. Increasing the concentration of pH with aquatic plant treatment after some time finally the wastewater can meet the environmental quality standard (BML) 6-9. The control group that was not given water plants, the initial concentration was pH 3.03, the pH on the first day was 3.30, the second and third days the concentration was the same, namely 3.30. There is an effect of absorption of water hyacinth and water lettuce on Cu and Zn content in plant tissues (leaves and roots).